Student response to mathematical concepts in context - McNaney, Danielle (Kansas State University, 2009)
In recent years motivation research has emerged as an area of interest within educational research. Increasing student achievement is not the only aspect of education being studied. Improving the quality of the learning experience and investigating how this improvement affects student achievement is an area of growing interest. Additional investigations also consider what aspects of instruction and teaching affect the quality of the learning experience. Many mathematical organizations have voiced a concern that post-secondary mathematics courses should adapt curriculum and instruction based on results of this research. The current study is an investigation into the effectiveness of suggestions made by these organizations, as well as the effect instructional adaptations have on student attitude and achievement.
Keywords: Motivation; Mathematics in context; Student attitude; Affect; Education, Mathematics (0280)